An Evaluation of Age Determination in Forensic Medicine Using Scoring of the Epiphyses at the Knee Joint on Radiographs - Akkuş Çetinkaya, Tuba; Avşar, Abdullah; Kızıldağ, Betül (The Bulletin of Legal Medicine, 2023)
Objective:Age estimation is also widely used in identification. The aim of study is to investigate applicability of age determination method in Türkiye by examining the radiographs of the knee joint and using the epiphyseal scoring based on the degree of epiphyseal closure. Methods: Knee graphs of 676 cases (337 women, 339 men) aged between 10 and 26 years were retrospectively analyzed. Distal femur (DF), proximal tibia (PT), and proximal fibula (PF) epiphyseal lines were evaluated separately in each case. The closure of the epiphyses was studied at 3 stages. DF, PT and PF epiphyses were graded 0, 1, 2 for stage 1, 2 and 3 respectively. These three scores obtained in each case were collected and the score of the epiphyses at the knee joint (SKJ) was obtained.Results: The median age in each of the SKJs increased in both men and women. The difference between the genders was statistically significant according to the median age of 0-5 points (p
Keywords: adli tıp, yaş tayini, kronolojik yaş, görüntüleme yöntemi, diz eklemi